Application of bronchoscope for the placement of nasoenteric feeding tube: new ideas from old ways - Wu, Ching Feng; Chao, Yin-Kai (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
The novel technique of nasoenteric feeding tube (NET) placement with bronchoscope proposed by Cao et al. (1) is an interesting report and deserve in depth discussion and further study. In spite of limited case numbers, Cao et al. validate that placing nasojejunal tube with bronchoscope is safe and feasible in post esophagectomy patients.